2022
DOI: 10.1186/s12891-022-05983-6
|View full text |Cite
|
Sign up to set email alerts
|

Cerclage performance analysis – a biomechanical comparison of different techniques and materials

Abstract: Background Wire cerclages play a fundamental role in fracture fixation. With an increasing variety of designs being commercially available the question arises which cerclage should be used. This study investigates the biomechanical properties of metallic and non-metallic cerclages and their different application-types. Furthermore, potential influence of muscular interposition between bone and cerclage constructs was tested. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…For example, Förch et al reported the superior biomechanics of cable cerclage in addition to a plate osteosynthesis of distal tibia fracture (3). Hägerich et al reported that the non-metallic cerclage provides similar stability to metal cerclage and reduces metallic risk profile (4). Nevertheless, the stainless steel wire remains the most common cerclage material because of surgeon familiarity, cost-effectiveness, and reliable biomechanical property.…”
mentioning
confidence: 99%
“…For example, Förch et al reported the superior biomechanics of cable cerclage in addition to a plate osteosynthesis of distal tibia fracture (3). Hägerich et al reported that the non-metallic cerclage provides similar stability to metal cerclage and reduces metallic risk profile (4). Nevertheless, the stainless steel wire remains the most common cerclage material because of surgeon familiarity, cost-effectiveness, and reliable biomechanical property.…”
mentioning
confidence: 99%